Analysis Of The Effectiveness Of Village Revenue And Expenditure Budget Management (Krueng Simpo Village, Juli District) - Murti Sari Dewi; Nurul Amini; Farhati; Zuhra Syahrul; Putri Azzuhra (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the effectiveness of managing the Village Revenue and Expenditure Budget (APBDes) in Gampong Krueng Simpo, Juli Sub-district, Bireuen Regency. The research employed a qualitative descriptive approach with data collected through interviews, observation, and documentation. Data were analyzed interactively through reduction, display, and conclusion drawing techniques. The findings indicate that APBDes management in Gampong Krueng Simpo is relatively effective in terms of planning, implementation, and supervision. This is reflected in community participation during village planning meetings, budget transparency, and the alignment of development programs with predetermined plans. Furthermore, village officials play active roles, and supervision is carried out systematically by Tuha Peut. However, some challenges remain, including limited human resources in information technology, low community involvement in monitoring, and external factors such as geography and weather affecting the implementation of physical projects. Overall, the 2024 fiscal year demonstrates a balanced and healthy village financial management, oriented toward community empowerment and the development of local economic potential.